About the compliance of white cabbage varieties and hybrids with the real demand of population - B. M. Molokov (Овощи России)
Relevance. The actual demand for cabbage is based on the demographic composition of the Russian population. Based on this provision, the weight size of marketable, in particular, midripening cabbage, in the range from 1 to 3 kg, is justified. However, until now, domestic breeding firms are focused on the creation of hybrids with increased yields, not taking into account the real demand of the population.Materials and methods. The studies were carried out on mid-season hybrids of white cabbage of the fifth maturation group SB-3 F1 and Kuizor F1 in vegetable-growing farms of the NonChernozem zone of the Russian Federation typical for that time: "Bykovo" and "Agrofirma" Podmoskovnoe".Results. Studies on the mid-season hybrid SB-3 F1 showed that the share of commercial heads of cabbage ranged from 32.9-44.1%, reaching 73.3% in only one technological variant. The share of commercial heads in hybrids of foreign selection Kuizor F1 was 97%. A radical way to meet the requirements of the population is the creation of mid-season hybrids with different dynamics of growth of the marketable mass of heads of cabbage and, accordingly, with different lengths of the growing season. This is necessary to ensure the receipt and sale of marketable products – biologically ripe heads of cabbage weighing 1-3 kg within 2-3 months of the summer-autumn period. At the same time, obtaining such heads of cabbage should be ensured by the genetic potential of hybrids.